Detecção e rastreamento de leucócitos em imagens de microscopia intravital via processamento espaçotemporal - Silva, Bruno César Gregório da (2016)
Over the last few years, a large number of researchers have directed their efforts and interests for the in vivo study of the cellular and molecular mechanisms of leukocyte-endothelial interactions in the microcirculation of many tissues under different inflammatory conditions. The main goal of these studies is to develop more effective therapeutic strategies for the treatment of inflammatory and autoimmune diseases. Nowadays, analysis of the leukocyte-endothelial interactions in small animals is performed by visual assessment from an intravital microscopy image sequences. Besides being time consuming, this procedure may cause visual fatigue of the observer and, therefore, generate false statistics. In this context, this work aims to study and develop computational techniques for the automatic detection and tracking of leukocytes in intravital video microscopy. For that, results from frame to frame processing (2D – spatial analysis) will be combined with those from the three-dimensional analysis (3D=2D+t – spatio-temporal analysis) of the volume formed by stacking the video frames. The main technique addressed for both processings is based on the analysis of the eigenvalues of the local Hessian matrix. While the 2D image processing aims the leukocyte detection without worrying about their tracking, 2D+t processing is intended to assist on the dynamic analysis of cell movement (tracking), being able to predict cell movements in cases of occlusion, for example. In this work we used intravital video microscopy obtained from a study of Multiple Sclerosis in mice. Noise reduction and registration techniques comprise the preprocessing step. In addition, techniques for the analysis and definition of cellular pathways comprise the post processing step. Results of 2D and 2D+t processing steps, compared with conventional visual analysis, have shown the effectiveness of the proposed approach.